Recent Advances in the Catalytic Conversion of Biomass to Furfural in Deep Eutectic Solvents - Zhang, Xu; Zhu, Peng; Li, Qinfang; Xia, Haian (Frontiers in Chemistry, 2022)
Lignocellulose is recognized as an ideal raw material for biorefinery as it may be converted into biofuels and value-added products through a series of chemical routes. Furfural, a bio-based platform chemical generated from lignocellulosic biomass, has been identified as a very versatile alternative to fossil fuels. Deep eutectic solvents (DESs) are new ‘green’ solvents, which have been employed as green and cheap alternatives to traditional organic solvents and ionic liquids (ILs), with the advantages of low cost, low toxicity, and biodegradability, and also have been proven to be effective media for the synthesis of biomass-derived chemicals. This mini-review summarizes the recent advances of DESs in the conversion of carbohydrates to furfural, which mainly focus on the effect of adding different catalysts to the DESs system, including metal halides, water, solid acid catalyst, and certain oxides, on the production of furfural. Moreover, the challenges and prospective of DESs-assisted furfural synthesis in biorefinery systems are also discussed in this mini-review.